2016
DOI: 10.1007/s10339-016-0754-9
|View full text |Cite
|
Sign up to set email alerts
|

Emerging adults’ sleep patterns and attentional capture: the pivotal role of consistency

Abstract: College students face consistent cognitive demands and often get insufficient and/or irregular sleep. The current study investigated associations of sleep duration and sleep variability with attentional performance. Sleep duration variability was expected to moderate the association between duration and cognitive functioning. College students' (n = 83) natural sleep patterns were recorded via wristband actigraphy across three consecutive nights during an academic term. The association between sleep duration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Greater sleep variability has been negatively associated with health (e.g., higher body mass index: Moore et al, 2011), mood (e.g., poorer subjective well-being: Lemola et al, 2013; increased severity of depression: Suh et al, 2012), and behaviour (e.g., adolescent aggression: Lemola et al, 2012). Of particular relevance to the current study, Whiting and Murdock (2016) demonstrated that sleep duration variability moderates the association between sleep duration and attentional disengagement, that is, the capacity to withdraw attention from the currently focused stimulus (attentional switch). Shorter sleep duration was associated with poorer ability to switch attention when coupled with low sleep duration variability.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Greater sleep variability has been negatively associated with health (e.g., higher body mass index: Moore et al, 2011), mood (e.g., poorer subjective well-being: Lemola et al, 2013; increased severity of depression: Suh et al, 2012), and behaviour (e.g., adolescent aggression: Lemola et al, 2012). Of particular relevance to the current study, Whiting and Murdock (2016) demonstrated that sleep duration variability moderates the association between sleep duration and attentional disengagement, that is, the capacity to withdraw attention from the currently focused stimulus (attentional switch). Shorter sleep duration was associated with poorer ability to switch attention when coupled with low sleep duration variability.…”
Section: Introductionmentioning
confidence: 74%
“…Sleep variability has been broadly defined as inconsistencies in various sleep indices including sleep onset and offset timing, sleep latency, sleep quality, wake after sleep onset, sleep duration, and efficiency. It is typically calculated as the variability from weekdays to weekends (Lemola et al, 2012) or as the within-subject standard deviation for the corresponding variables over the course of several days (Whiting & Murdock, 2016) to weeks (Lemola et al, 2013; Lev Ari & Shulman, 2012; Sánchez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the impact of prior sleep and wake on test battery performance during shifts, participant sleep-wake characteristics in the 24 hours prior to the start of the day, first and subsequent (3 rd , 4 th or 5 th ) night shift associated with testing were calculated from actigraphy. For this analysis only, missing actigraphic sleep data were substituted with data from sleep diaries as per previous studies 39 to ensure sufficient power. Subjective sleep timing was determined from self-reported sleep onset and sleep offset times.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, performance in several objective EF tests is associated with circadian rhythm and time of day, suggesting that sleep timing may play a part in performance-based EF (Hahn et al, 2012). Similarly, irregular sleep, as night-to-night variation in sleep, has been shown to associate with more frequent attention problems (Whiting and Murdock, 2016) and subjective wellbeing (Lemola et al, 2013). Also, sleep variability may account for some of the sleep-related decline in cognitive performance, especially in emerging adults (Whiting and Murdock, 2016).…”
mentioning
confidence: 99%
“…Similarly, irregular sleep, as night-to-night variation in sleep, has been shown to associate with more frequent attention problems (Whiting and Murdock, 2016) and subjective wellbeing (Lemola et al, 2013). Also, sleep variability may account for some of the sleep-related decline in cognitive performance, especially in emerging adults (Whiting and Murdock, 2016).…”
mentioning
confidence: 99%